Student Engagement in an Inter-Departmental Learning Community Assessing Skills of Children With Intellectual Disabilities (Journal on Excellence in College Teaching, 2024)
In a paired-course project, students from psychology and special education collaborated to assess skills of children with intellectual disabilities. In this mixed-methods study, the researchers (1) administered measures of student engagement and career decision making to students pre- and post-project and (2) coded student journals for engagement and perceptions. Results included positive effects on teacher-student and peer relationships, as well as positive perceptions of the learning community. The authors offer recommendations for how the project could be expanded to teach students multi-disciplinary skills relevant to their future occupations.